1979
DOI: 10.1111/j.1540-4560.1979.tb00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Abortion: A Social‐Psychological Perspective

Abstract: More than most medical procedures, abortion is embedded in a social context that has implications for psychological reactions of patients. Following a brief history of legislation and research on abortion, correlates of post‐abortion reponses are reviewed. A social‐psychological framework is suggested which views abortion as a stress experience. Responses to the experience will be a function of the nature and meaning of the pregnancy to the individual woman, her defensive and coping style, and the social envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 38 publications
(38 reference statements)
2
30
0
Order By: Relevance
“…As a result, the conclusions drawn by researchers and writers were frequently influenced by the strong negative emotional and social beliefs about abortion (Adler, David, Major, Roth, Russo & Wyatt, 1990, 1992. Simon and Senturia (cited in Adler, 1979) concluded that 'deeply held personal convictions frequently seem to outweigh the importance of the data, especially when conclusions are drawn' (p. 103).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…As a result, the conclusions drawn by researchers and writers were frequently influenced by the strong negative emotional and social beliefs about abortion (Adler, David, Major, Roth, Russo & Wyatt, 1990, 1992. Simon and Senturia (cited in Adler, 1979) concluded that 'deeply held personal convictions frequently seem to outweigh the importance of the data, especially when conclusions are drawn' (p. 103).…”
Section: Introductionmentioning
confidence: 95%
“…The research findings reflected the generally accepted belief that abortion was beyond the range of 'normal' experience. Kummer (cited in Adler, 1979), noted that the frequent reference in medical literature to post-abortion psychiatric illness was not based on sound research. His review ofthe literature led him to conclude that this widely held belief was a myth resulting from the enforcement of a taboo against abortion.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Information in the form included study type (prospective, retrospective, or comparison); date of data collection; country in which the investigation was performed; selected details concerning the demographics, sampling, and follow-up methodology; incidence of women reported to have had a negative.or neutral/positive postabortion experience; the dependent variable used to determine outcome; the mean score and statistical test results performed on quantitative outcome measures; and a compilation of the methodological limitations of each study. The form was designed to validate and amplify information in existing review articles (Adler, 1979;David, 1972David, , 1978Doane & Quigley, 1981;Gibbons, 1984;Handy, 1982;Heath, 1971;Illsley & Hall, 1976;Keasling & Davis, 1975;Mudd, 1973;Olley, 1973;Olson, 1980;Pariser, Dixon, & Thatcher, 1978;Pohlman, 1970;Raphael, 1972aRaphael, , 1972bShusterman, 1976;Walter, 1970;White, 1966).…”
Section: Standard Summary Formmentioning
confidence: 99%